PENERAPAN MODEL PEMBELAJARAN PETA PIKIRAN DALAM PEMBELAJARAN MENULIS CERITA PENDEK - Febri Restu Widianto; Sukma Murni (STKIP Siliwangi, 2020)
Short stories are stories that have a short physical appearance. Generally, the numbers are around 500-5,000 words. Mind map is the utilization of the whole brain by using visual images and other graphic infrastructure to form a deeper impression. The purpose of this study to 1) Know the learning of short story writing before giving treatment 2) Know the learning of short story writing after being given treatment 3) Know the difference in learning outcomes of short story writing on students who learn by using traditional learning models with students who learn by using mind map learning models. Methodologically, this study uses a quasi-experimental method with a mind map learning model. The use of mind maps is intended so that students can more easily create a writing framework before writing a short story in its entirety. This is the reference for students in writing short stories. Then students begin to compile the story by referring to the mind map framework they made, by referring to aspects of the short story including aspects of content, aspects of structure, and aspects of language rules. From the entire series of research conducted, it can be concluded that there are differences in learning outcomes of short story writing from class XI students of SMA Negeri 4 Cimahi who learn by using a mind map learning model better than those using conventional learning models.